Aplikasi Edmodo dan Minat Siswa Sekolah Dasar Dalam Pembelajaran Online : Pengujian Model Delone & Mclean - Hudi, Mustofa; Zulherman, Zulherman (Jurnal Paedagogy, 2023)
This study aims to analyze the effect of using the Edmodo application on students’ interest in online learning by testing the Delone & McLean model. This research method used an analytical survey with a quantitative approach. The population in this study were students of Duren Sawit 13 Pagi Elementary School, with a total sample of 92 students according to the measurement of the G*Power application, which consisted of VA, VB, and VC graders. This research instrument used a questionnaire via a Google Form. The data analysis technique used was the reliability test, validity test, and hypothesis testing using the SmartPLS application. The results of this study indicated that of the eight hypotheses tested, only two were accepted. In comparison, the other six hypotheses were rejected, meaning that the Edmodo application could not increase elementary school students’ interest in online learning. It is caused by many students having difficulty using the application, students being less active during the learning process, lack of interaction between teachers and students, and not all students having adequate internet access. In contrast, this application was very dependent on the internet.